2017
DOI: 10.1016/j.zoolgart.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Behaviours in Two Captive Brown Bear ( Ursus arctos Linnaeus, 1758) Females: Individual Differences and Seasonal Variations

Abstract: Abnormal behaviours are common in captive environments that not supply the physical and psychological needs of animals. There are animals, like brown bears, more susceptible to develop abnormal behaviours due to their seasonal biology related to food, hibernation or reproduction. The two brown bear Ursus arctos females from Barcelona Zoo, Spain, showed two different patterns of abnormal behaviours. The old ♀ displayed episodes of biting a tree trunk while the young ♀ carried out headtossing events. The studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Of particular concern are the relatively high prevalence and rates of stereotypic behaviour shown by zoo elephants (e.g., swaying, weaving, pacing [Mason and Veasey 2010]), felids [Quirke et al 2012;Vaz et al 2017], primates [Pomerantz et al 2012], bears [Soriano et al 2017], polar bears (Ursus maritimus) [Shepherdson et al 2013]) found 85% of bears in their study performed the behaviour and it used up an average of 11% of the activity budget, and minks (Polanco et al 2018), among others. Broom (1983) suggested that it is unacceptable for any animal to spend more than 10% of the waking day displaying abnormal behaviours.…”
Section: Animal Behaviour Stereotypies and Environmental Enrichmentmentioning
confidence: 99%
“…Of particular concern are the relatively high prevalence and rates of stereotypic behaviour shown by zoo elephants (e.g., swaying, weaving, pacing [Mason and Veasey 2010]), felids [Quirke et al 2012;Vaz et al 2017], primates [Pomerantz et al 2012], bears [Soriano et al 2017], polar bears (Ursus maritimus) [Shepherdson et al 2013]) found 85% of bears in their study performed the behaviour and it used up an average of 11% of the activity budget, and minks (Polanco et al 2018), among others. Broom (1983) suggested that it is unacceptable for any animal to spend more than 10% of the waking day displaying abnormal behaviours.…”
Section: Animal Behaviour Stereotypies and Environmental Enrichmentmentioning
confidence: 99%
“…Changes in the behavior of captive animals when the natural environment is not available, or not similar such as in nature, were examined from 4 articles [4] [16][18] [19].…”
Section: Abnormal Behaviormentioning
confidence: 99%
“…Dental health can be disturbed due to the appearance of caries. Especially for animals that have a habit in cleaning their teeth with bone or wood [4] [19]. Stress level are caused by increased glucocorticoid hormone secretion in the blood.…”
Section: Inadequate Nutritionmentioning
confidence: 99%
See 1 more Smart Citation